The Efficacy of Electrolysed Oxidising Water for Inactivating Spoilage Microorganisms in Process Water and on Minimally Processed Vegetables - Ongeng, Duncan; Devlieghere, Frank; Debevere, Johan; Cooseman, Jozef; Ryckeboer, Jaak (International Journal of Food Microbiology, 2006)
The efficacy of Electrolysed Oxidising Water (EOW) for inactivating spoilage microorganisms in process water and on minimally processed vegetables was investigated. The direct effect of EOW on three important spoilage bacteria namely; Pseudomonas fluorescens, Pantoea agglomerans or Rahnella aquatilis was determined by inoculating tap water or “artificial process water” with approximately 8 log CFU/ml pure culture and electrolysing the resultant solutions. The three bacteria were each reduced to undetectable levels at low (0.5 A) and relatively higher levels (1.0 A) of current in tap water and “artificial process water”, respectively. The residual effect of EOW on P. fluorescens, P. agglomerans or R. aquatilis was determined by incubating at room temperature 1 ml (approximately 9 log CFU/ml) pure culture suspensions in 9 ml of EOW-T (EOW produced from tap water), EOW-A (EOW produced from “artificial process water” supplemented with approximately 60.7 mg Cl−/l and 39.3 mg Na+/l) or deionised water (control) for 0, 15, 45 or 90 min. The bactericidal activity of both EOW-T and EOW-A increased with the concentration of free oxidants and incubation period and the three bacteria were completely reduced at free oxidants-incubation period combinations of 3.88 mg/l–45 min and 5.1 mg/l–90 min in EOW-T and EOW-A, respectively. Two types of industrial vegetable process water; salad-mix and soup process water, which had each a total psychrotrophic count of approximately 8 log CFU/ml were then electrolysed. Without any NaCl addition, only 1.2 and 2.1 log reductions of the psychrotrophs in soup and salad-mix process water was attained respectively. Supplementation of the process water with approximately 60.7 mg Cl−/l and 39.3 mg Na+/l afterwards resulted in complete reduction of the psychrotrophic count in both process waters, but soup process water required relatively higher levels of current compared to salad-mix water. Finally, fresh-cut lettuce was washed in EOW-T containing 3.62 mg free oxidants/l, EOW-IP (EOW produced from industrial process water) containing 2.8 mg free oxidants/l or tap water (control) for 1 or 5 min. Washing the vegetables for 1 min in EOW-T resulted in 1.9, 1.2, and 1.3 log reductions of psychrotrophs, lactic acid bacteria and Enterobacteriacae, respectively, which increased to 3.3, 2.6, and 1.9 log reductions after washing for 5 min instead. EOW-IP tested in this work had no bactericidal effect on the microflora of fresh-cut lettuce. Electrolysis could therefore be used to decontaminate process water for vegetable pre-washing and to sanitise tap water for final rinsing of vegetables, respectively.
Keywords: : Electrolysed oxidising water; Decontamination; Pseudomonas fluorescens; Pantoea agglomerans; Rahnella aquatilis; Process water; Minimally processed vegetables